Thermal, magnetic and spectral studies of metal-quinone complexes Part III. radical coordination and hydrogen bonding mediated exchange interaction in copper-hydroxyquinone complex - Salunke-Gawali, S.; Rane, S. Y.; Boukheddaden, K.; Codjovi, E.; Linares, J.; Varret, F.; Bakare, P. P. (Journal of Thermal Analysis and Calorimetry, 2005)
The reaction of CuCl with 2HNQ, ( viz. 2- hydroxy- 1,4- naphthoquinone), in methanol results in [Cu-2( II, II)(4HNSQ)(2)(ONQ)(2)(H2O)(4)], Cu- 3 complex; [ where ONQ is the deprotonated oxidized form of ligand ( viz. 2- oxido- 1,4- naphthoquinone) and 4HNSQ one electron reduced tautomeric form of the ligand (i.e. 4- hydroxy - 1,2- naphthosemiquinone)]. The mixed valent redox ligation is confirmed in [ 9] by us. In present report complex Cu- 3 investigated by variable temperature magnetic susceptibility measurements ( SQUID), X and Q- band EPR, DSC and CV techniques. A break is observed in the chi(m)(-1) vs. T plot similar to 200 K in Cu- 3 which is attributed to a phase transition. In Cu- 3 a quintet state ( S= 2) is populated above 200 K by the molecular association of two exo Cu( II)( 4HNSQ) units via hydrogen bonding between Cu(ONQ) unit of endo ligands in dimer. Magnetic susceptibility data is treated with tetramer model with S= 1/2,1/2,1/2,1/2. The interdimer triplet- triplet interaction ( J) in two [ Cu( 4HNSQ)] units and intradimer ( zJ(1)) interaction between [ Cu( II)( 4HNSQ)] are best fitted with J= -50 cm(-1) and zJ(1)= 28 cm(-1), respectively, using g= 2.2. `Quintet- triplet' phase transition occurs with an enthalpy change of 31.83 kJ mol(-1) estimated from DSC. Cu( II)double left right arrow Cu( I) and NSQ double left right arrow CAT redox couples at E-1/2= 0.68 V and E-1/2 = -1.12 V, respectively are result of exo ligands and Cu( II) ions interaction, while shifts of ligand based peaks viz. NQ -> NSQ and NSQ double left right arrow CAT at - 0.44 and - 0.67 V towards positive potential on complexation are due to electron transfer interactions between endo ligand and Cu( II) ion.
Keywords: antiferromagnetic coupling; copper complexes; Lawsone; model complexes; quinones; triplet state